Predictors of psychological well-being among Indonesian teachers during the covid-19 pandemic - Baoninang, Yosep Gabriel Hoeng (Animo Repository, 2023)
This mixed-method explanatory sequential study aimed to determine and explore the predictive role of locus of control and self-efficacy on psychological well-being among 384 Indonesian high school teachers during the COVID-19 pandemic. The participants completed self-report surveys through a web-based information system, followed by in-depth interviews for ten participants to explain the findings in the quantitative data. Applying the multiple linear regression to identify the relationship between the predictive and criterion variables indicated that the internal locus of control positively and significantly predicts Indonesian high school teachers' psychological well-being (t = 2.380; p0.077) and by chance (t = 1.758; p>0.079), statistically did not predict the psychological well-being of Indonesian high school teachers. In addition, the result showed that teachers' sense of self-efficacy positively and significantly predicts the psychological well-being of Indonesian high school teachers (t = 7.018; p Keywords: psychological well-being, internal locus of control, external locus of control, self-efficacy